ANALISA BANGKITAN PERGERAKAN PADA KAWASAN LAMPULO KOTA BANDA ACEH - Suriyadi Suriyadi; Renni Anggraini; Azmeri Azmeri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: Urban development is a series that can not be separated from the overall development activities in the framework of space and time. Increasing population Lampulo district, district of Kuta Alam, Banda Aceh has increased the movement of traffic flows towards and out of the area. Increased movement occurs primarily from 06.00 to 08.00 am, noon 13:30 pm to 14:30 pm, afternoon from 17.00 to 19.00. A trip generation modeling stage that estimates the number of movements originating from Lampulo district. This study aims to find out about trip generation patterns in the region Lampulo, and to determine the most dominant mode of transportation used to pattern Lampulo of trip in the region, which is reviewed by a mandatory activity, maintenance, and discretionary. Observations carried out on people in the area Lampulo, through questionnaires as many as 93 families. The results showed that the factors affecting the movement of activity mandatory requirement is the number of family members working (X5). The resulting regression model is Y1 = - 0.500 + 1,750X5. Factors affecting the movement needs of maintenance activity is the number of family members of the school (X6). The resulting regression model is Y2 = 1.388 + 0,500X6. Factors affecting the movement needs of discretionary activity is the number of cars in the family (X4) and the number of family members of the school (X6). The resulting regression model is Y3 = 0.838 + 0,419X4 + 0,189X6. Factors affecting the movement needs of all events is the number of motorcycles in the family (X3) and mileage (X7). The resulting regression model is Y = 2,215 + 0,479X3 + 0,051X7. The dominant mode of transportation in the movement of the mandatory activities, maintenance, and discretionary in Lampulo region is the mode of motorcycles.Abstrak: Kegiatan pembangunan kota merupakan suatu rangkaian yang tidak dapat dipisahkan dari kegiatan pembangunan secara keseluruhan dalam rangka ruang dan waktu. Meningkatnya jumlah penduduk kawasan Lampulo, Kecamatan Kuta Alam, Kota Banda Aceh telah meningkatkan pergerakan arus lalulintas menuju dan keluar kawasan. Peningkatan pergerakan terjadi terutama mulai pukul 06.00 s/d 08.00 WIB, siang hari pukul 13.30 WIB s/d 14.30 WIB, sore hari mulai pukul 17.00 s/d 19.00 WIB. Bangkitan pergerakan merupakan tahapan pemodelan yang memperkirakan jumlah pergerakan yang berasal dari kawasan Lampulo. Penelitian ini bertujuan untuk mengetahui tentang pola bangkitan perjalanan dalam kawasan Lampulo, serta untuk mengetahui moda transportasi yang paling dominan digunakan terhadap pola bangkitan perjalanan dalam kawasan Lampulo, yang ditinjau berdasarkan aktivitas mandatory, maintenance, dan discretionary. Observasi dilakukan pada penduduk di kawasan Lampulo, melalui penyebaran kuesioner sebanyak 93 KK. Hasil penelitian menunjukkan bahwa faktor yang mempengaruhi kebutuhan pergerakan dari aktivitas mandatory adalah jumlah anggota keluarga yang bekerja (X5). Model regresi yang dihasilkan adalah Y1 = - 0,500 + 1,750X5. Faktor yang mempengaruhi kebutuhan pergerakan dari aktivitas maintenance adalah jumlah anggota keluarga yang sekolah (X6). Model regresi yang dihasilkan adalah Y2 = 1,388 + 0,500X6. Faktor yang mempengaruhi kebutuhan pergerakan dari aktivitas discretionary adalah jumlah mobil dalam keluarga (X4) dan jumlah anggota keluarga yang sekolah (X6). Model regresi yang dihasilkan adalah Y3 = 0,838 + 0,419X4 + 0,189X6. Faktor yang mempengaruhi kebutuhan pergerakan dari semua aktivitas adalah jumlah sepeda motor dalam keluarga (X3) dan jarak tempuh (X7). Model regresi yang dihasilkan adalah Y = 2,215 + 0,479X3 + 0,051X7. Moda transportasi dominan pada pergerakan pada aktivitas mandatory, maintenance, dan discretionary di kawasan Lampulo adalah moda sepeda motor.